THE CORRELATION BETWEEN NURSE PERFORMANCE & THE LEVEL OF JAMKESMAS PATIENT SATISFACTION IN DAHLIA II WARD, NGUDI WALUYO WLINGI HOSPITAL - Wahyu Dini Metrikayanto (UNEJ e-Proceeding)
The main purpose of health service is toenhance degree of health and to prevent the diseasewith the main target were the society. There wereseveral public health assurances in Indonesia, suchas Jamkesmas, Jamkesda, SPM, Askes. People coulduses these assurance or with own payment.Jamkesmas was the social program from theIndonesian government for the poverty. Thisprogram organized nationally with the crosssubventionto gain the whole of health service inpoverty1.Poverty had same right with other people,including the right to get the health services. Manypeople felt that health service was so expensive. Thiscondition generates a barrier for the poverty.Government action to distribute health service forlow economic class was by applies JamkesmasProgram. This program was including public healthservice (Puskesmas) with their networks, like aadvance health service, emergency health service,and the other limited health services. Jamkesmasprogram was run in many health care service unitslike hospital, public health service, some privatehospital, etc.Nurse was the biggest number in of theseareas, and cares the patient in 24 hours. As a frontliner health provider, nurse performance was veryimportance in hospital success. Nurse performanceis means the work accomplishment done by nursewhen nurse care process, this include assessment,diagnose, intervention, implementation, andevaluation.Nurse performance can be evaluated by usingnursing practice standard. Nursing practice standardis norm or explanation about nurse work quality.Nurse work quality can be considered as good, right,or correct. This can be used as guideline for nursingpractice and evaluation of nurse performance3.The main purpose of Jamkesmas programwas to increase the access and quality of health carefor the poverty which could rise the people healthdegree optimally and efficiently4. In the other hand,some opinions consider that the service forJamkesmas patient was different.Ixora (2008) studied about the comparationof Social Safety Net (Jaring Pengaman Sosial) danNon Social Safety Net (Non Jaring Pengaman Sosial)perception in Seruni and Raflesia Ward, Dr.Soedomo Public Hospital, Treggalek showed thatmayority perception was negatif. This study taken in9 days with 40 respondents.Saputra (2010) studied about The Effect ofNurse Performance and Patien’s Satisfaction as theuser of Jamkesmas Card in RSUD Cengkareng, WestJakarta showed that nurse performance influencedpatient’s satisfaction. But, the questionair used inthis research was not based on nursing process,which includes; assesment, nursing diagnose,intervention, implementation and evaluation.Linder-Pelz (1982) in Krowinski and Stevens(1996), stated that client satisfaction was positiveevaluation in the scope of health services (caringprocess evaluated in single clinical visit, graduallymedical intervention, planning or health service andgeneral health service. Generally, patient satisfactionis showed by the suitable result with patient’s hopeduring or after service.Patient satisfaction was generated fromcomparation between hope and services duringhealth services in hospital. In this case, nurses hasgreat impact for the patient satisfaction. During 24hours nurses always dealing with patient. So, nurseperformance could be the patient attention.The patients of Jamkesmas program werepoverty. Some health problem were suffered fromthem such as tuberculosis, malaria, malnutrition,sexual transmitted disease, and the othercommunicable disease. Generally, these diseasecould be found in internal ward.From the preliminary studies in Dahlia IIWard, Ngudi Waluyo Wlingi Hospital on 05-06September 2012 by interviewed the head wardindicated that all of the Jamkesmas patient hadsame right and intervention with the other patient(non assurance or other assurance). But,administration process influenced the nurse timerespone to do nurse or medical intervention. Somerequirement should be prepared to claim theProceeding ICMHS 2016 ISBN 978-602-60569-3-1267medicines, medical tools, etc. More over, emergencyintervention could be delayed by this process.Patient perspective to health services indicatethe quality of nursing care. To understand the realcondition, researcher investigated the correlationbetween nursing performance & the level ofJamkesmas patient satisfaction in dahlia II ward,Ngudi Waluyo Wlingi Hospital.The aim of this research was to understandthe correlation between nursing performance & thelevel of Jamkesmas patient satisfaction in Dahlia IIward, Ngudi Waluyo Wlingi Hospital. Researcherexpected to this research could be usefull for thenurse, institution and researcher. Nurses wereexpected to enhance the performance while care theJamskesmas patient in Dahlia II ward, Ngudi WaluyoWlingi Hospital. Institution was expected to createpolicy for enhancing the performance while care theJamskesmas patient in Dahlia II ward, Ngudi WaluyoWlingi Hospital. Researcher was expected toimprove the insight and understanding related tonurse performance the level of Jamkesmas patientsatisfaction in dahlia II ward, Ngudi Waluyo WlingiHospital.